Educational Transformation: Implementation of Technology-Based Learning Models in Enhancing Critical Thinking Skills in Boarding School Environments - Valencia, Nadira Putri; Shodiq, Sadam Fajar (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
Implementing technology-based learning models is crucial for fostering students' critical thinking abilities inside a school dormitory setting. This research aims to assess the impact of technology-based learning models on the development of students' critical thinking skills at boarding schools located in Yogyakarta. This research included a sample of 298 students from boarding schools in Yogyakarta. This study employed quantitative methodologies, namely utilising a Likert scale survey. There were four boarding schools included in this research study. Researchers employed the SmartPLS version 4 technology to conduct experiments and validate this notion. The research findings demonstrated that the utilisation of technology in learning had a beneficial impact on students' aptitude for critical thinking. Implementing technology-based learning methods in boarding schools is essential to maintain a harmonious integration of technological advancements. However, it does not impede students' capacity to enhance their critical thinking abilities.